Respuesta :

Answer:

D

Step-by-step explanation:

Given

x² + 6x - 9 = 0 (add 9 to both sides )

x² + 6x = 9

Using the method of completing the square

add ( half the coefficient of the x- term )² to both sides

x² + 2(3)x + 9 = 9 + 9

(x + 3)² = 18 ( take the square root of both sides )

x + 3 = ± [tex]\sqrt{18}[/tex] = ± [tex]\sqrt{9(2)}[/tex] = ± 3[tex]\sqrt{2}[/tex]

Subtract 3 from both sides

x = - 3 ± 3[tex]\sqrt{2}[/tex] → D

Answer:

D

Step-by-step explanation:

  1. go look at the other answers on brainly you will see im right i am smart